THE INFLUENCE OF FINANCIAL PERFORMANCE, OWNERSHIP STRUCTURES, AND COMPANY SIZE TOWARD DEBT POLICY IN BANKING COMPANIES LISTED ON IDX - Angela, Angela (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
This study aims to examine the effect of financial performance, ownership structure, and company size on debt policy in banking companies listed on IDX for the 2019 period. The method used in this study is a quantitative method and the data used is obtained from the annual financial statements of banking companies listed on IDX. The data collection technique used the purposive sampling method. The results of this study indicate that financial performance as measured by ROA has a significant positive effect on debt policy. On the other hand, financial performance as measured by ROE has a significant negative effect on debt policy. Meanwhile, managerial ownership does not have a significant effect on debt policy and institutional ownership has a significant negative effect on debt policy. In addition, company size has a significant positive effect on debt policy.Keywords: Financial Performance; Ownership Structure; Company Size